Using circles games to investigate the referential use of negation. Issue 1 (2nd January 2023) - Capuano, Francesca; Dudschig, Carolin; Kaup, Barbara
ABSTRACT: Studies on the spontaneous production of negation suggest that it can be modulated by pragmatic principles of successful communication such as informativity and relevance. The present study investigates whether negation production is additionally modulated by a more general principle of effort minimisation. In a series of circles games, subjects were presented with pairs of circles and asked to complete a sentence that would allow a listener to identify one of the two circles. Negation was only produced when an affirmative description for the circle at issue was harder, i.e. there was no simple intuitive way to describe the circle's pattern. The length of the concurrent descriptions did not strictly influence the production of negation. The results suggest that the use of negation becomes more frequent as the effort to produce it decreases with respect to a concurrent affirmation, even at the cost of greater informativity of affirmation.